L’Architecture aujourd'hui est-elle encore un art ? Considérations théoriques et implications éthiques - Létourneau, Marie-Claude (Labyrinth, 2020)
Is Architecture Today Still an Art? Theoretical Considerations and Ethical Consequences Architecture has been proposing, for many decades now, more and more spectacular buildings. This could lead to believe that architecture has reached the top of its art. But this question requires first to define art in general, and also the authentic art of architecture. For this purpose, we will use a Bergsonian methodology in order to unveil in an unprecedented way the two different natures of art. The first nature, "ephemeral art", will be analyzed as an artistic performance, which is powered by the creative gesture. The second nature, "persistent art", relies on durable productions. Using a multidisciplinary approach, we will create links between the two natures of art and German musicology: "pathogenic" and "logogenic" architectural productions will be presented to validate if architecture respects its own profound nature. We will finally analyze the modern paradigm of occidental "occulocentric" way of creating with its lack of hermeneutic substance and, thus, its important ethical consequences.